Identification of a novel InDel locus within the ACSL5 gene and its association with body measurement traits in goats - A. Wang; A. Wang; A. Wang; X. Wu; X. Wu; Q. Xu; B. Wang; T. Xiao; Y. Liu; W. Li (Archives Animal Breeding)
The ACSL5 (acyl-CoA synthetase 5) gene plays a crucial role in the biosynthesis of triglycerides, phospholipids, and cholesterol as well as the metabolism of fatty acids, and goats derive approximately 80 % of their energy from volatile fatty acids. However, there is a limited number of studies on the impact of InDel (insertion/deletion) mutations in the ACSL5 gene on goat traits. Therefore, This study investigated the spatiotemporal expression pattern of ACSL5 in goats and the association between its polymorphism and growth traits, aiming to identify useful DNA markers and provide a basis for the application of marker-assisted selection (MAS) in goat breeding. The qPCR technique was employed in the expression profiles of the ACSL5 gene in Fuqing (FQ) goats. The PCR technique was employed for type detection of the InDel locus of the ACSL5 gene in 528 goats. We analyzed the genotype frequency, allele frequency, polymorphism information content (PIC), and Hardy–Weinberg equilibrium (HWE) of the InDel locus of the ACSL5 gene in goats. A general linear model was used to analyze the relationship between the genotypes and body size traits of goats. qPCR analysis indicated that the ACSL5 gene was expressed ubiquitously in the nine tested tissues of FQ goats. The expression level of ACSL5 in fat tissue at birth was higher than in adult (P<0.01) and weaning (P<0.05) goats. An InDel polymorphism termed del41712 was detected within the fifth intron of the ACSL5 gene. Genetic screening revealed only two genotypes, ID and II, present in the three studied goat breeds. Association analyses conducted on 528 goats linked this InDel polymorphism to body measurement traits, showing significant associations with chest depth (ChD) in FQ goats (P<0.05) and with body height (BH), body length index (BLI), and chest circumference index (ChCI) in Nubian (NB) goats (P<0.05). These findings suggest that InDel mutations in the goat ACSL5 gene may serve as a valuable molecular genetic marker for breeding programs aimed at improving production traits.